ANALYSIS OF THE IMPLEMENTATION OF MANAGEMENT FUNCTIONS IN THE BACI 1 FARMER GROUP ORGANIZATION: INHIBITING FACTORS AND EFFORTS TO IMPROVE PERFORMANCE - Hj.Aidah; Jumria (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal